Digital literacy-based community empowerment in the public service information system in Makassar City - Nur Wahid; Arni Arni; Sitti Rahmawati Arfah; A Khusnul Khatimah; Andi Ummul Resky Lutfiah (Universitas Muhammadiyah Magelang, 2024)
This service activity aims to enhance people's knowledge and skills in effectively utilizing digital technology. Community empowerment through public service information refers to initiatives that aim to improve public access to services and deliver relevant information more efficiently. The method employed in this activity consists of three stages: 1) preparation through community-wide socialization for effective coordination, 2) implementation conducted through counseling sessions, and 3) evaluation performed by distributing pre-test and post-test questionnaires to assess the knowledge and skills of partners regarding the digital literacy training in public services that has been conducted. During the evaluation stage, the success of the activity is gauged by distributing questionnaires. The results of this service demonstrate that 90% of participants experienced an increase in skills related to the procedures for accessing digital public services through a dedicated website for reporting public service issues.